2005
DOI: 10.1038/sj.cdd.4401792
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic surface delivery of K+ channels

Abstract: Apoptosis in cortical neurons requires efflux of cytoplasmic potassium mediated by a surge in Kv2.1 channel activity. Pharmacological blockade or molecular disruption of these channels in neurons prevents apoptotic cell death, while ectopic expression of Kv2.1 channels promotes apoptosis in non-neuronal cells. Here, we use a cysteine-containing mutant of Kv2.1 and a thiol-reactive covalent inhibitor to demonstrate that the increase in K þ current during apoptosis is due to de novo insertion of functional chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
111
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 27 publications
3
111
0
Order By: Relevance
“…In addition, syntaxin is known to bind to the most proximal region of the Kv2.1 C terminus, termed C1a, during Ca 2+ -facilitated exocytosis in pancreatic and other nonneuronal cells (47)(48)(49). Importantly, we showed that syntaxin is also required for the membrane insertion of Kv2.1 channels during apoptosis (23). Based on these observations, and because CaMKII is also necessary for the K + current increase, we hypothesized that an interaction between CaMKII and syntaxin would be detected in our system.…”
Section: Injurious Oxidant Exposure Leads To Camkii Activation In Neumentioning
confidence: 67%
See 2 more Smart Citations
“…In addition, syntaxin is known to bind to the most proximal region of the Kv2.1 C terminus, termed C1a, during Ca 2+ -facilitated exocytosis in pancreatic and other nonneuronal cells (47)(48)(49). Importantly, we showed that syntaxin is also required for the membrane insertion of Kv2.1 channels during apoptosis (23). Based on these observations, and because CaMKII is also necessary for the K + current increase, we hypothesized that an interaction between CaMKII and syntaxin would be detected in our system.…”
Section: Injurious Oxidant Exposure Leads To Camkii Activation In Neumentioning
confidence: 67%
“…Here, we report that Ca 2+ and Zn 2+ signals do, in fact, converge on a cellular event critical for the K + current enhancement, and that CaMKII is required for this process. However, CaMKII does not act upstream of p38 activation as originally hypothesized, but instead interacts with the N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) protein syntaxin, which we showed to be necessary for the insertion of Kv2.1-encoded K + channels following an apoptotic stimulus (23).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…4 indicate that two distinct declustering stimuli, actin depolymerization and dephosphorylation, do not increase channel activity, although it is possible we have not used the optimal stimulus or that HEK cells do not fully mimic the in situ regulation. One interesting area for future research will be to examine the effect of apoptotic stimuli on Kv2.1 activation because this channel is essential for this oxidant-induced cell death (11,25). Additional declustering stimuli will include N 2 saturated solutions as a means of establishing hypoxia (26).…”
Section: Discussionmentioning
confidence: 99%
“…The threshold for activation of Kv2.1 is shifted to more negative potentials in response to various excitatory stimuli (e.g., glutamate, ischemia, muscarinic activation, elevated cytoplasmic Ca 2+ ); it is presumably via this mechanism that Kv2.1 selectively regulates neuronal excitability during periods of high-frequency excitotoxic stimuli (8)(9)(10). Kv2.1 also plays a well-established role in apoptosis (11), where it may mediate the KCl loss involved in cell death.…”
mentioning
confidence: 99%